2015
DOI: 10.1245/s10434-015-4678-x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Resection of Remnant Gastric Cancer Following Distal Gastrectomy: A Retrospective Clinicopathological Study

Abstract: The prognosis of patients with RGC can be improved by aggressively performing curative resection without causing complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…This was expected because lymph node dissection had already been performed during the initial surgery in group M. In the current study, both groups showed the same incidence of lymph node metastasis. In previous reports, however, the incidence of lymph node metastasis was higher in group B [6,[18][19][20]. This could be explained by the fact that the number of remaining lymph Modified based on the extent of LN dissection for primary tumor according to the Japanese Gastric Cancer Treatment Guidelines and the Japanese Classification of Gastric Carcinoma a Lymph nodes dissected for D1: nos.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This was expected because lymph node dissection had already been performed during the initial surgery in group M. In the current study, both groups showed the same incidence of lymph node metastasis. In previous reports, however, the incidence of lymph node metastasis was higher in group B [6,[18][19][20]. This could be explained by the fact that the number of remaining lymph Modified based on the extent of LN dissection for primary tumor according to the Japanese Gastric Cancer Treatment Guidelines and the Japanese Classification of Gastric Carcinoma a Lymph nodes dissected for D1: nos.…”
Section: Discussionmentioning
confidence: 94%
“…Together, these findings indicate that, despite progress in intensive therapies, the therapeutic outcomes for advanced CRS have hardly changed at all over the past 20 years. In a comparison of a more recent period with a prior period, Takahashi et al found a better survival rate in the more recent period [20]. These findings do not show an improvement in therapeutic outcomes, but they do indicate that better diagnostic abilities have increased the number of CRSs that are discovered early.…”
Section: Discussionmentioning
confidence: 97%
“…Although the number of patients who undergo surgery for benign gastric diseases has been reduced, the early detection of PGC and improvements in the prognosis of PGC patients lead to an increase in the incidence of RGC . While the standardization of RGC surgery and the development of multiple adjuvant treatment therapies have improved the survival rate of RGC patients, the 5‐year survival rate of RGC patients is still 10%‐90% for those who have different tumor features, and as high as 27%‐36% of RGC patients relapse after surgery . To compare the survival of remnant gastric cancer (RGC) with primary gastric cancer, a systematic literature search was performed using PubMed with the keywords “remnant,” ‘‘stomach” and “cancer,” revealing 1065 relevant reports published up to the end of December 2018.…”
Section: Discussionmentioning
confidence: 99%
“…Newly developed gastric cancer after partial gastrectomy for benign disease or gastric cancer is de ned as remnant gastric cancer or gastric stump cancer (GSC), which is found in 1.1-6% of patients [2][3][4][5][6]. Complete resection of the carcinoma combined with a radical lymph node dissection is the only way to secure curability and improve the prognosis in patients who have no other complications [7]. Mesenteric lymph node metastasis around the gastrojejunostomy may worsen the prognosis of GSC [5].…”
Section: Introductionmentioning
confidence: 99%